How can a language learner be successful in second or third language acquisition? - Huszti Ilona; Густі Ілона (PoliPrint Kft., 2009)
A jelen tanulmányban vázolt kutatás arra kereste a választ, segít-e valakinek a második vagy harmadik nyelv tanulásában az, ha már sikeresen elsajátított egy idegen nyelvet. Esetként egy olyan fiatal tanárt választottam, aki az anyanyelvén kívül három másik nyelvet is tanult. A kapott kutatási eredmények teljes mértékben alátámasztják a téma szakirodalmából ismert bizonyított tényeket, miszerint ha valaki ért már el sikereket egy idegen nyelvnek a tanulásában, annak a második vagy harmadik nyelv elsajátítása már nem okozhat különösebb gondot.

Резюме. У статті розлядається питання, чи допоможе студентові знання іноземної мови при вивченні другої або третьої іноземної мови. Дослідження було проведено з молодим викладачем-лінгвістом, який володів трьома (іноземними) мовами. Результати доказали, що попередні успіхи з вивчення іноземної мови позитивно впливають на вивчення та засвоєння другої або третьої іноземної мови, упростовуючи навчальний процес.

Abstract. The research question of the present study is defined as follows: What are the strategies used by a language learner in a special language environment where at least three languages (Hungarian, Ukrainian and Russian) are simultaneously in use. The expectation was that previous knowledge of a foreign language (in this case — Russian) helped the subject in learning a third language (i.e. Ukrainian). The author aimed at identifying the strategies and techniques used by the learner during the process of learning the second and third language, investigating the subject’s feelings about his own language learning experience, and exploring factors (e.g. previous knowledge of foreign language) influencing the person’s achievements in learning a third language.
https://www.kmf.uz.ua/hun114/letoltes/acta/acta2009_2.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/92483
Keywords: language learning; success; second language; third language